Sequence–Activity Relationships for the Snf7 Insecticidal dsRNA in Chrysomelidae - Bachman, Pamela; Fridley, Jennifer; Mueller, Geoffrey; Moar, William; Levine, Steven L. (Frontiers in Plant Science, 2020)
The responsiveness of insects to oral delivery of insecticidal dsRNA has been shown to be dependent on dsRNA length and sequence match. Previous work with the western corn rootworm (WCR, Diabrotica virgifera virgifera; Coleoptera: Chrysomelidae) demonstrated that at least one 21 nt match must be present in the DvSnf7 dsRNA of approximately ≥60 base-pairs (bp) for activity. Further data is needed on the activity of <21 nt matches along with characterization of relationship between activity and the number of 21 nt matches. To characterize the sequence-activity relationship for insecticidal dsRNA further, the activity of orthologous Snf7 dsRNAs with 19-, 20-, and 21 nt contiguous matches against WCR were compared. Neither 19- or 20 nt sequence matches were active, supporting that a ≥21 nt sequence match is required for activity. The relationship between the number of 21 nt matches with activity of Snf7 dsRNA orthologs from several Chrysomelid species was characterized using WCR and Colorado potato beetle (CPB, Leptinotarsa decemlineata; Coleoptera Chrysomelidae). For WCR, there was a strong relationship between an increasing number of 21 nt matches and increased activity (i.e., lower LC50 values). A similar relationship was observed for CPB with an exception for a single ortholog, which may be related to the exceptionally high rate of polymorphisms in CPB. Overall, these results demonstrate a general relationship between the number of 21 nt matches and activity, and this relationship could be used to inform a testing and assessment plan for an ecological risk assessment for an insecticidal dsRNA.